Media Coverage of Female Candidates' Traits in the 2020 Democratic Presidential Primary. (2nd January 2022) - Cassese, Erin; Conroy, Meredith; Mehta, Dhrumil; Nestor, Franchesca
ABSTRACT: The 2020 Democratic presidential primary featured more female candidates than any prior race of its kind, presenting a unique opportunity to analyze media coverage of women running for this distinctively masculine office. In this article, we explore themes in trait coverage for female candidates in 2020. Using a natural language processing (NLP) approach, we analyze a sample of print and online media coverage of the Democratic primary field just prior to the Iowa Caucus. We find that trait coverage largely emphasized warmth and competence, with a tendency to criticize female candidates for displaying insufficient warmth. Comparing white women to women of color, we find coverage of Harris, but not Gabbard, emphasizes racial and gender identifiers. The themes emerging from our trait analysis suggest women candidates continue to face obstacles in the form of gendered and sometimes racialized media coverage on their paths to the presidency.